COVID-19 pandemic and other factors associated with unfavorable tuberculosis treatment outcomes—Almaty, Kazakhstan, 2018–2021 - Gabdullina, Malika; Maes, Edmond F.; Dzhazybekova, Panagul; Amanova, Gulzhan N.; Zikriyarova, Sanam M.; Nabirova, Dilyara; Horth, Roberta Z. (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic negatively influenced the availability of tuberculosis (TB) services, such as detection, diagnosis and treatment, around the world, including Kazakhstan. We set out to estimate the COVID-19 pandemic influence on TB treatment outcomes by comparing outcomes among people starting treatment before the pandemic (2018–2019) and during the pandemic (2020–2021) and to determine risk factors associated with unfavorable outcomes. Methods We conducted a retrospective cohort study among all people newly diagnosed with drug-sensitive pulmonary or extrapulmonary TB at least 18 years old who initiated treatment from 2018 to 2021 in Almaty. We abstracted data from the national electronic TB register. Unfavorable treatment outcomes were ineffective treatment, death, loss to follow-up, results not evaluated, and transferred. We used multivariable Poisson regression to calculate adjusted relative risk (aRR) and 95% confidence intervals (95%CI). Results Among 1548 people newly diagnosed with TB during the study period, average age was 43 years (range 18–93) and 52% were male. The number of people initiating treatment was higher before than the pandemic (935 vs. 613, respectively). There was significantly different proportions before compared to during the pandemic for people diagnosed through routine screening (39% vs. 31%, p < 0.001), 60 years and older (16% vs. 22%, p = 0.005), and with diabetes (5% vs. 8%, p = 0.017). There was no difference in the proportion of HIV (8% in both periods). Unfavorable outcomes increased from 11 to 20% during the pandemic (aRR = 1.83; 95% CI: 1.44–2.31). Case fatality rose from 6 to 9% (p = 0.038). Risk factors for unfavorable TB treatment outcomes among all participants were being male (aRR = 1.44, 95%CI = 1.12–1.85), having HIV (aRR = 2.72, 95%CI = 1.99–3.72), having alcohol use disorder (aRR = 2.58, 95%CI = 1.83–3.62) and experiencing homelessness (aRR = 2.94, 95%CI = 1.80–4.80). Protective factors were being 18–39 years old (aRR = 0.33, 95%CI = 0.24–0.44) and 40–59 years old (aRR = 0.56, 95%CI = 0.41–0.75) compared to 60 years old and up. Conclusion COVID-19 pandemic was associated with unfavorable treatment outcomes for people newly diagnosed with drug-sensitive TB in Almaty, Kazakhstan. People with fewer comorbidities were at increased risk. Results point to the need to maintain continuity of care for persons on TB treatment, especially those at higher risk for poor outcomes during periods of healthcare service disruption.